Swordsmanship «Intelligentsias»: Literary and Political Implications of Fencing in the Venezuelan «Fin de Siècle» (Castilla. Estudios de Literatura, 2024)
This article explores the political and aesthetic impacts of the popularity of fencing in Venezuela at the end of the 19th century. To do this, La esgrima moderna (1892), a pedagogical treatise written by the Venezuelan positivist José Gil Fortoul (1861-1943), is taken as the object of study. As will be attempted to be demonstrated, fencing drives certain ethical aspects of the national literature of the early 20th century, establishes a visual imaginary regarding male and female bodies, and becomes contradictory in the midst of the political transformations and repressions that arose during the dictatorship of Juan Vicente Gómez (1908-1935).
Keywords: venezuelan positivism; fencing; venezuelan literature; sport; latin american modernity